2013
DOI: 10.1002/2013jc009113
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on tidal mixing along the shelf break in the Green Belt in the southeastern Bering Sea

Abstract: 1] Tidal mixing and its associated iron and nutrients flux from a subsurface layer along the shelf break has been considered as one of the key processes to maintain the high summertime biological productivity in the Green Belt in the southeastern Bering Sea. In the present study, tidal mixing near the shelf break is examined with a three-dimensional highresolution numerical model to quantify the enhanced mixing and to reveal the underlying physical mechanisms based on the different characteristics of diurnal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…The percentage of local dissipation may be systematically higher in marginal seas or areas where lower modes are not free to escape (St. Laurent 2008;Nagai and Hibiya 2015). Similarly, near-field tidal dissipation can be increased by topographically trapped internal waves generated by subinertial tidal constituents (Tanaka et al 2013), that is, the diurnal constituents at latitudes >30° and the semidiurnal constituents at latitudes >74.5°. The energy density in such trapped motions increases with latitude and is all dissipated locally (Musgrave et al 2016).…”
Section: N E Ar -Fie Ld Tidal M Ixingmentioning
confidence: 99%
“…The percentage of local dissipation may be systematically higher in marginal seas or areas where lower modes are not free to escape (St. Laurent 2008;Nagai and Hibiya 2015). Similarly, near-field tidal dissipation can be increased by topographically trapped internal waves generated by subinertial tidal constituents (Tanaka et al 2013), that is, the diurnal constituents at latitudes >30° and the semidiurnal constituents at latitudes >74.5°. The energy density in such trapped motions increases with latitude and is all dissipated locally (Musgrave et al 2016).…”
Section: N E Ar -Fie Ld Tidal M Ixingmentioning
confidence: 99%
“…On the continental shelf, CTWs are typically bottom intensified at the shelf break, except in the limiting case of weak stratification (Crawford and Thomson 1984). Tanaka et al (2013) found enhanced bottom dissipation at the shelf break of the Bering Sea due to D1 trapped waves with bottom-intensified velocities, which contributed to the nutrient supply and productivity of the shelf. Irreversible mixing from shear instabilities can occur when the gradient Richardson number, Ri 5 N 2 /k›u/›zk 2 , is less than a critical threshold of 0.25 (e.g., Ivey et al 2018).…”
Section: Implications Of D1 Trapped Wavesmentioning
confidence: 86%
“…f . Both subinertial and superinertial waves may have a combined effect on mixing near topography (Musgrave et al 2016(Musgrave et al , 2017Stashchuk and Vlasenko 2017;Waterhouse et al 2017), with potential implications for the biological productivity of the shelf via enhanced fluxes of nutrients (e.g., Tanaka et al 2013). However, as trapped waves are highly dependent on the characteristics of the topography and stratification (Huthnance 1978), the role of these waves in modifying mixing will vary by region and seasonally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, recent work has sought to examine the energetics of these trapped waves as an important component of ocean processes near topography and at the basin boundaries (Tanaka et al 2010;Niwa and Hibiya 2011;Müller 2013;Tanaka et al 2013;Fer et al 2015;Klymak et al 2016;Musgrave et al 2017;Li et al 2017;Masunaga et al 2017;Hughes and Klymak 2019). Many authors (including this author) have calculated energy fluxes or constructed energy budgets for subinertial trapped internal tides by undertaking the same analysis that has been successfully applied to superinertial tides over a flat bottom (e.g., Kang and Fringer 2012).…”
Section: Introductionmentioning
confidence: 99%